Theru-K- Koothu and the disenchanted world: Paths and mispaths of a ritual tradition (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article addresses the dilemmas faced by the artists of Theru-K-Koothu, folkloric theatrical form of the state of Tamil Nadu, India, when displaced from their ritual, community and agrarian context, and launched into a globalized and urban world, where the collective imaginary and social organization differ from that where this cultural manifestation was gestated. Thus, analyzes the consequences and ramifications of this clash between two very different value systems on the artists, its networks and on the very structure of the performance, taking as argument the concept of “disenchantment of the world” of Weber, advancing to the dimension that the concept gets in the writings of Fischer-Lichte, in connection with the concept of “liminality” expressed by Caballero. The question that arises from this unusual encounter is: what can Theru-K-Koothu tell us about our own disenchantment and what strategies can it offer us as an antidote to it?
Keywords: Theru-K-Koothu; Folk Theatre; India; Performance Studies